2014
DOI: 10.1071/fp13299
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in stem sugar content and metabolism in sorghum genotypes subjected to drought stress

Abstract: Changes in stem sugar concentrations due to drought stress at the early reproductive stage were studied in seven sorghum (Sorghum bicolor (L.) Moench) genotypes that differ in their stem sugar storage ability. Total sap sugar concentration increased in most genotypes. ANOVA showed a significant contribution of genotype and treatment to the variation in sugar levels. Two genotypes showed little variation in total sugar levels at the fifth internode from the peduncle and five genotypes showed significant increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…Stem-reserves have been recognized as an important source of carbon for grain-filling, when photosynthesis is inhibited by the abiotic stresses such as heat and drought (Blum, 1998 ). Accumulation of sugars in stem has been predicted to be an adaptive strategy against different stresses, as found in different genotypes of sorghum under the drought stress (Quazi et al, 2014 ). Asthir and Bhatia ( 2014 ) have reported that HS causes built-up of total free sugars and decreases the starch content of grains in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…Stem-reserves have been recognized as an important source of carbon for grain-filling, when photosynthesis is inhibited by the abiotic stresses such as heat and drought (Blum, 1998 ). Accumulation of sugars in stem has been predicted to be an adaptive strategy against different stresses, as found in different genotypes of sorghum under the drought stress (Quazi et al, 2014 ). Asthir and Bhatia ( 2014 ) have reported that HS causes built-up of total free sugars and decreases the starch content of grains in wheat.…”
Section: Discussionmentioning
confidence: 99%
“…; Qazi et al . ). Hence the adaptation of sorghum to drought through mobilisation of soluble sugars appears to be genotype‐dependent.…”
Section: Introductionmentioning
confidence: 97%
“…There are reports that stem reserves in sorghum contribute to grain filling under drought stress conditions, during which photosynthesis is inhibited (Blum et al 1997). However in some sorghum genotypes, the losses in grain yields and stem sugars due to drought stress were similar, indicating that the panicle and stems serve as independent sinks, both being affected by source limitation (Gutjahr et al 2013b;Qazi et al 2014). Hence the adaptation of sorghum to drought through mobilisation of soluble sugars appears to be genotype-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…Since C4 grasses can be grown on marginal lands not suitable for most food crops, the high biomass producing vegetative tissues of sorghum, miscanthus, and sugarcane are desirable targets for engineering efforts aimed at producing and/or storing lipids (Carlsson et al , 2011; Sanjaya et al , 2011; Weselake, 2016a; Lima et al , 2017). For example, stem tissues engineered to divert energy from nonstructural carbohydrates into the lipid biosynthesis pathway through strategies such as increasing the supply of FAs, increasing TAG assembly activities, and blocking TAG breakdown pathways have resulted in higher amounts of TAGs accumulating in vegetative tissues (Papini-Terzi et al , 2009; Waclawovsky et al , 2010b; Sanjaya et al , 2011; Qazi et al , 2014; Sekhon et al , 2016). Other proof-of-concept studies for increasing TAGs in vegetative tissues have been performed in Arabidopsis thaliana, Brachypodium distachyon, Nicotiana benthamiana, Nicotiana tabacum , sugarcane ( Saccharum spp.…”
Section: Introductionmentioning
confidence: 99%